The essential and optimal analgesic and anti-inflammatory medicines for athletes at the olympic games - Stuart, M.; Farooq, M.; Thomas, T.; Mohamed-Ali, N.; Al-Maadheed, M.; Mohamed-Ali, V. (Sports Medicine - Open, 2024)
Background In 2019, the International Olympic Committee published the first Olympic and Paralympic Model Formulary (OPF), which defined the standardised set of medications required at every Olympic and Paralympic Games for the treatment of athletes. This study aimed to test the OPF to determine whether it meets the clinical needs of the athlete population with respect to medications used for pain and/or inflammation (PI), and to present a revised set of essential PI medications for the OPF based on prevalence of athlete use. Medication-use data of athletes at the Tokyo 2020 and Beijing 2022 Olympic Games (n=6155) from three sources were used to establish prevalence of PI medicine use and to revise the OPF: (i) doping control forms, (ii) pharmacy dispensing reports, and (iii) injection declaration forms. This revised list was further validated through (iv) medication importation declarations by teams (n=156), and (v) survey of team physicians (n=382).